Islamic Leadership Training: A panacea for Economic Growth and safeguard to Democracy in Nigeria - Ibrahim Alhaji Isa; Muhammad Nazifi Inuwa (Phd); Farida Mahmoud Abdussalam (Penerbit Hellow Pustaka, 2025)
The paper discusses the need for Islamic leadership training as a solution for Economic Growth and safeguard to Democracy in Nigeria. It begins by outlining the economic challenges facing the country, such as high rate of abject poverty, inflation, corruption, weak economy, weedy political governance, insecurity and unemployment. It equally explains how economic problem has contributed to the rise of political instability and violence in Nigeria. Furthermore, the paper employs qualitative analysis where literary sources are used from print and e-materials. The study explains the conventional and Islamic concept of leadership. It stresses that Islamic leadership training can help to address these challenges by promoting economic justice and creating opportunities for people to participate in the political process. In conclusion, the paper emphasizes on the importance of Islamic leadership training in Nigerian political setting and recommends among others that Nigerian leaders should intensify their efforts to address the interests of the poor people across the country. This is because poor people who are hungry coupled with lack of education, good health, and shelter might not be interested in voting or engage in other electoral responsibilities.